Avena fatua caryopsis dormancy release is associated with changes in KAR(1) and ABA sensitivity as well as with ABA reduction in coleorhiza and radicle - Kępczyński, Jan (Planta, 2021)
MAIN CONCLUSION: The dormancy release in Avena fatua caryopses was associated with a reduction in the ABA content in embryos, coleorhiza and radicle. The coleorhiza proved more sensitive to KAR(1) and less sensitive to ABA than the radicle. The inability of dormant caryopses and ABA-treated non-dormant caryopses to complete germination is related to inhibition and delayed of cell-cycle activation, respectively. ABSTRACT: As freshly harvested Avena fatua caryopses are dormant at 20 °C, they cannot complete germination; the radicle is not able to emerge. Both karrikin 1 (KAR(1)) and dry after-ripening release dormancy, enabling the emergence of, first, the coleorhiza and later the radicle. The after-ripening removes caryopse sensitivity to KAR(1) and decreases the sensitivity to abscisic acid (ABA). The coleorhiza was found to be more sensitive to KAR(1), and less sensitive to ABA, than radicles. Effects of KAR(1) and after-ripening were associated with a reduction of the embryo’s ABA content during caryopsis germination. KAR(1) was found to decrease the ABA content in the coleorhiza and radicles. Germination of after-ripened caryopses was associated with the progress of cell-cycle activation before coleorhiza emergence. Inhibition of the germination completion due to dormancy or treating the non-dormant caryopses with ABA was associated with a total and partial inhibition of cell-cycle activation, respectively.